Visualization of altered neurovascular coupling in chronic stroke patients using multimodal functional MRI - Blicher, J; Blicher, J; Stagg, C; O'Shea, J; Østergaard, L; MacIntosh, B; Johansen-Berg, H; Jezzard, P; Donahue, M; Donahue, M; Donahue, M (2012)
Evaluation of cortical reorganization in chronic stroke patients requires methods to accurately localize regions of neuronal activity. Blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) is frequently employed; however, BOLD contrast depends on specific coupling relationships between the cerebral metabolic rate of oxygen (CMRO 2), cerebral blood flow (CBF), and volume (CBV), which may not exist following stroke. The aim of this study was to understand whether CBF-weighted (CBFw) and CBV-weighted (CBVw) fMRI could be used in sequence with BOLD to characterize neurovascular coupling mechanisms poststroke. Chronic stroke patients (n11) with motor impairment and age-matched controls (n11) performed four sets of unilateral motor tasks (60 seconds/30 seconds off/on) during CBFw, CBVw, and BOLD fMRI acquisition. While control participants elicited mean BOLD, CBFw, and CBVw responses in motor cortex (P=0.01), patients showed only mean changes in CBF (P=0.01) and CBV (P=0.01), but absent mean BOLD responses (P=0.20). BOLD intersubject variability was consistent with differing coupling indices between CBF, CBV, and CMRO 2. Thus, CBFw and/or CBVw fMRI may provide crucial information not apparent from BOLD in these patients. A table is provided outlining distinct vascular and metabolic uncoupling possibilities that elicit different BOLD responses, and the strengths and limitations of the multimodal protocol are summarized. © 2012 ISCBFM All rights reserved.